Roles of the multifunctional glycoprotein, emmprin (basigin; CD147), in tumour progression - Yan, Li; Zucker, Stanley; Toole, Bryan P. (Thrombosis and Haemostasis, 2005)
Emmprin (basigin;CD147) is a widely distributed cell surface glycoprotein that belongs to the Ig superfamily and is highly enriched on the surface of malignant tumour cells. Emmprin is involved in numerous physiological and pathological systems and exhibits several molecular and cellular characteristics, but a major function of emmprin is stimulation of synthesis of several matrix metalloproteinases. In tumours, emmprin most likely stimulates matrix metalloproteinase production in stromal fibroblasts and endothelial cells as well as in tumour cells themselves by a mechanism involving homophilic interactions between emmprin molecules on apposing cells or on neighbouring cells after membrane vesicle shedding. Membrane-associated cofactors, including caveolin-1 and annexin II, regulate emmprin activity. Emmprin induces angiogenesis via stimulation of VEGF production, invasiveness via stimulation of matrix metalloproteinase production and multidrug resistance via hyaluronan-mediated up-regulation of ErbB2 signaling and cell survival pathway activities. Although the detailed mechanisms whereby it regulates these numerous phenomena are not yet known, it is clear that emmprin is a major mediator of malignant cell behavior.
Keywords: Matrix metalloproteinases; angiogenesis; invasiveness; chemoresistance; tumour-stroma interaction